Using Mathematical Models in Secondary Grammar Schools - Kézi, Csaba (International Journal of Engineering and Management Sciences, 2023)
On February 11, 2021, I gave a motivational lecture at the Tamás Esze High School in Mátészalka, and I completed a series of test tasks with the students. In this article, I looked for an answer to how students who are about to graduate approach to solving math problems. The main objective was to investigate whether they prefer to solve purely mathematical or application-oriented tasks, and in which one they achieve better results. In this paper, I analyze the results obtained.